Studi Literatur: Pengaruh Tingkat Pendidikan, Pengalaman Kerja Serta Skeptisme Profesional Auditor Terhadap Kualitas Audit - Indah Ananda Rayza Putri; Aristanti Widyaningsih; Nelly Nur Apandi (JURNAL ECONOMINA, 2024)
The purpose of this study was to determine whether or not there was an influence of each independent variable, namely the level of education, work experience, and professional skepticism of auditors on audit quality. The method used was a literature review method using library research techniques to collect data. Articles that passed the selection were then used for analysis of the main topics to be discussed. The results of the analysis showed that there were pros and cons to the influence of the level of education or work experience on audit quality. Meanwhile, the influence of professional skepticism has a positive impact on audit quality. This is because the audit process needs to be accompanied by the auditor's skeptical nature in order to find unusual findings. Further research is recommended to examine other indicators that can affect audit quality.